Influences on the Spatial Directivity of Acoustic Vector Sensor by Finite Cylinder Baffle and Future Prospects About Eliminating the Effects - 嵇建飞 梁国龙 庞福滨 张光普 (Shanghai jiao tong da xue xue bao, 2012)
The directivity of acoustic vector sensor can be distorted by the sound diffraction wave of baffle. According to Helmholtz integral equation, the directivity of acoustic vector sensor under the condition of finite cylinder baffle is calculated by using boundary element method （BEM）. Considering the problem of nearly singular integrals of BEM, the exponent parts of fundamental solutions axe expanded in trigonometric functions. The singular and the nonsingular parts are separated： the nonsingular parts are calculated by Gaussian integral method; the singular parts are regularized by subsection integral method. Then the surface integrals are reduced into line integrals along the elements＇ contour which can be calculated by Gaussian integral method. The sound diffraction field of a plane wave under the condition of finite cylinder baffle at different frequencies and incident angles is calculated, and the characteristics of directivity of pressure and vibration velocity at different frequencies are analyzed. The experimental data are treated and the errors between the experimental and theoretical results are analyzed. Finally, according to the research results about the influences on the directivity of acoustic vector sensor by baffle at present, some future prospects about eliminating the effects of sound diffraction field by baffle are presented.